Production of furfural and levulinic acid from purple Cameroon grass (Pennisetum purpureum cv. Morado) by a two-stage process (2024)
The purple Cameroon grass crop (P. purpureum cv. Morado) presents signifcant potential as a source of raw materials and renewable energy; it has rapid growth, high yield, and low fertilizer demand. During the conversion of lignocellulosic biomass, hemicellulose and cellulose can frst be hydrolyzed into fve and six-carbon sugars, and then the sugars are converted into furfural and levulinic acid (LA) respectively. In this work, the furfural and levunilic acid production was evaluated in a two-stage catalytic process with a tin catalyst supported on a sulfonated activated carbon. In the frst stage, a furfural yield of 23.28% at 170 °C for 3 h. In the second stage, the efect of process temperature and time on LA production's yield and energy demand was evaluated; LA yield of 28.17% was obtained with an energy demand of 0.12 kWh/gLA at 180.47 °C for 1.78 h. These results demonstrate the possibility of obtaining furfural from Cameroon grass.